Perspectives of use of microcomputer Raspberry Pi in effective Kazakhstan digitalization - Ospanova, А. Б.; Tuleuov, Б. И. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2018)
In the paper the popular among developers single-board computer Raspberry Pi is considered. The research projects on the basis of Raspberry Pi 3 Model B and Raspberry Pi Zero models providing, according to authors, rational decisions in the fields of activity requiring use of specialized hardware software support or the considerable hardware computing resources are offered, developed and described. The projects are devided into the following three groups according to the idea integrating them formulated in the paper: portable automated experts workplace; versatile budgetary computer class and specialized laboratory; the specialized hardware software devices protected from unauthorized access. Stages and content of projects implementation are developed and provided. The hardware requirements and also necessary configurations of devices for implementation of each project are defined and described.